PENGARUH PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN KETERAMPILAN PROSES SAINS PESERTA DIDIK SD - Neviasari, Wendi; Anggoro, Subuh; Dyah Purwandari, Ristiana; Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking skills and science process skills among elementary school studentsremain relatively low, as observed in Grade III of SD Negeri Tritih Kulon 09,Panjaitan Cluster, North Cilacap District, where students had never conductedsimple experiments, formulated hypotheses, or carried out scientific inquiry on themetamorphosis topic due to teacher-centered instruction. This study analyzes theeffect of the Problem Based Learning (PBL) model on critical thinking skills andscience process skills, while examining the relationship between the two variables.The study employed a quantitative approach with a quasi-experimental design(Nonequivalent Control Group Design), involving 51 Grade III students divided intoan experimental group (28 students from SD Negeri Tritih Kulon 09) and a controlgroup (23 students from SD Negeri Tritih Kulon 06). Data were collected throughtests, interviews, and documentation, and analyzed using the Mann–Whitney U Testsince the data did not meet the assumptions of normality and homogeneity. Resultsshow that PBL had a significant effect on both critical thinking skills (Mean Rankexperimental 36.89 vs. control 12.74; Sig. = 0.000) and science process skills (MeanRank experimental 34.52 vs. control 15.63; Sig. = 0.000), with mean gains of 26.61and 16.07 points in the experimental group, while the control group declined on bothvariables. This study provides empirical evidence that PBL can develop criticalthinking skills and science process skills in an integrated, simultaneous mannerwithin a single learning topic, a focus rarely addressed in previous PBL studies,which have generally examined the two variables separately.